1995
DOI: 10.1111/j.1348-0421.1995.tb02254.x
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity of Trichothecene Mycotoxins (Deoxynivalenol, Fusarenon‐X, and Nivalenol) against Herpes Simplex Virus Types 1 and 2

Abstract: The effect of trichothecene mycotoxins, deoxynivalenol (DON), fusarenon-X (FX) and nivalenol (NIV), on plaque formation of herpes simplex virus types 1 and 2 (HSV-1 and HSV-2) in HEp-2 cells was examined. The 50% effective concentrations (EC50) of DON, FX, and NIV for HSV-1 plaque formation were 160, 56, and 120 ng/ml, respectively.Those for HSV-2 plaque formation were 94, 26, and 50 ng/ml, respectively. These three mycotoxins showed about 2-fold higher selectivity to HSV-2 than to HSV-1. Plaque formation of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Although these trichothecenes have been associated to various biological properties, such as antibiotic, antimalarial and antileukemic activities and immunotoxic effects [1], [2], [3], [4], very few studies on their antiviral activity have been reported. Both simple (nivalenol, deoxynivalenol, fusarenon, T-2 toxin and related compounds) and macrocyclic (satratoxin G, roridin A and baccharinoids B-4 and B-5) trichothecenes were found to inhibit the replication of Herpes simplex virus [5], [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…Although these trichothecenes have been associated to various biological properties, such as antibiotic, antimalarial and antileukemic activities and immunotoxic effects [1], [2], [3], [4], very few studies on their antiviral activity have been reported. Both simple (nivalenol, deoxynivalenol, fusarenon, T-2 toxin and related compounds) and macrocyclic (satratoxin G, roridin A and baccharinoids B-4 and B-5) trichothecenes were found to inhibit the replication of Herpes simplex virus [5], [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…(Sudakin 2003), and from some higher plants such as Bacchairis artemisioides and Baccharis coridifolia (Habermehl et al 1985;Rizzo et al 1997), Ficus fistulosa and Rhaphidophora decursiva (Zhang et al 2002). Biologically, macrocyclic trichothecenes were reported to be antileukemic (Jarvis et al 1980(Jarvis et al , 1984, antimalarial (Isaka et al 1999;Zhang et al 2002), antimicrobial (Liu et al 2006;Wagenaar and Clardy 2001), antiviral (Tani et al 1995), phytotoxic and cytotoxic (Abbas et al 2002;Masuda et al 2007), and some were reported to possess animal toxicity (Hughes et al 1989). In the present study, the two trichothecenes (compounds 1 and 2), obtained from the EtOAc extract of the fungus JS9 isolated from the marine sponge Axinella sp., were ascertained to be antifungal compounds with the MICs comparable with those of fluconazole.…”
Section: Resultsmentioning
confidence: 95%
“…In our work, T2‐toxin ( 1 ) and the mixture of 8‐ n ‐butyryl‐ neo solaniol ( 2 ) and 8‐isobutyryl‐ neo solaniol ( 3 ) were shown for the first time to present activity against P. brasiliensis . Some trichothecene mycotoxins have several biological properties, such as antiviral (Herpes Simplex Virus type 2 and type 1), antibiotic, antimalarial, antileukaemic, and immunotoxic 43–49 …”
Section: Discussionmentioning
confidence: 99%